The Role of Consumers' Emotions in Online Impulse Buying of Fashion Apparel - Calvin Smith; Chloé C. Kabamba (International Journal of Business and Social Science Research, 2022)
This study examined emotions as predictors of subsequent buying behavior. The primary aim of this research was to investigate consumers’ experience of impulsive buying in the online shopping environment and the influence that emotions have on these experiences, focusing on fashion apparel.  Hypotheses were developed around the premise that emotions play a prominent role in everyday decisions, including an individual’s impulsive decisions and buying behavior. The study used a self-administered 10-item questionnaire to test the hypotheses.  One hundred and twenty-eight people (N=128; 55% men, 45% women) from various parts of the world, with persons aged between 18 and 34 (77.34%) most represented, completed the survey. The data revealed a strong correlation between negative emotions and impulse buying, and between low arousal of negative emotions and impulse buying. Other results and implications are discussed.